The De-Politicization of Social Policy at the Time of Social Investment. Mechanisms and Distinctive Features - Busso, Sandro (PARTECIPAZIONE E CONFLITTO, 2017)
Social policy has undergone a major process of de-politicization all over Europe in the last twenty years, that was fostered by the paradigm shift towards the so-called Social Investment Welfare State. Though similar processes are taking place in many policy areas, social policy can be considered one of the most promising fields of observation of de-politicization. The downgrading of the political character of decision making, indeed, is in sharp contrast with the relevance of the debate about values and justice and with the conflicts that accompanied the establishment of welfare systems. The paper argues that de-politicization is the result of the interaction between three different mechanisms: the shift of emphasis from justice to effectiveness and the model of "governance by numbers"; the process of individualization of social intervention that marginalized collective responsibilities; the inclusive model of governance that co-opt civil society organizations reducing their role as conflicting actors. The three mechanisms give way to a model of de-politicization distinguished by the narrowing of the political debate about solutions, models of intervention and principles, based on inclusion rather than delegation and in which political ac-tors do not disappear. The process of de-politicization is relatively independent from the trend of re-trenchment that begins with the political success of neoliberalism. However, as we will see, it is essential to the survival of its principles.